Evaluasi Sifat Fisikokimia Mie Basah Dengan Subsitusi Tepung Tulang Ikan Bandeng (Chanos chanos) - Rini Rahayu Sihmawati; A. Wardah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2021)
Milkfish bone waste from the thornless milkfish industry contains have sufficient protein, calcium and phosphorus element. The milkfish bones can be processed and used as fish bone meal which is used as a substitute for processed foods, including wet noodles. This study aims to evaluate the physicochemical analysis of noodles wet. The research design used was a completely randomized design with one factor, namely the formulation of. milkfish bone meal to substitute for wheat, with the composition, F0 (100:0), F1 (95:5), F2 (90 :10), F3 (85:15) and F4 (80:20). Research observations include water content, protein content, water absorbtion, dough expantion and texture. The results were analyzed by analysis of variance (ANAVA) and the smallest significant difference (BNT) if, there was a difference at the 5% level of significance. The substitution formulation of milkfish bone meal had a significant effect on all parameters.The more addition of milkfish meal.the higher the protein content will increase the rate protein content and the water content, water absorption,dought expantion and texture are lower.Base on the protein content, it is recommended to add 20% fish bone meal because it has the highest protein content. The best treatment for water content, water absorption, dough expantion and texture was the addition 0f 5% fish bone meal. Keywords: Substitution, fish bone meal, wet noodles, physicochemical analisis